Four new species of Hysterocinetida (Protozoa: Ciliophora) from the digestive tract of earthworms collected to the lower Nyong estuary (South Coast, Cameroon) - Nana, Paul Alain; Tchakonte, Simeon; Mama, Anselme Crepin; Onana, Fils Mamert; Fokam, Zephyrin; Ngassam, Pierre; Masseret, Estelle; Nola, Moïse; Sime-Ngando, Telesphore (Zootaxa, 2022)
Hysterocinetida are a large assemblage of ciliates characterized by sucker and buccal apparatus. They have a wide distribution in the digestive tract of oligochaete annelids of the genus Alma that inhabit hydromorphic parts of non-anthropic hydrosystems. On the basis of morphological, morphometric and infraciliature characteristics revealed by ammoniacal silver carbonate and 4’,6-Diamidino-2-Phenyl Indole (DAPI) staining techniques, four forms were identified as new members belonging to three genera: Preptychostomum, Proptychostomum and Thurstonia. Preptychostomum donendaensis n. sp. is ovoid with a slightly narrowed anterior part and is commensal to the digestive tract of Alma emini and A. nilotica. There are 20–23 kineties on the lower side and 42–45 on the upper side. Proptychostomum gigas n. sp. is pear-shaped, with a narrowed anterior part and a wide posterior part (125–138 µm × 80–85 µm). There are 40 to 44 kineties, equally distributed on both sides of the ciliate. Its sucker is circular and measures 31–34 µm in diameter. The peristome follows the contour of the cell and the infundibulum has a turn of spire. Thurstonia emini n. sp. is identified in the digestive tract of A. emini. The cell is elongate, with the anterior pole narrower than the truncate posterior pole (90–115 µm × 40–55 µm). The kineties are equally distributed on both sides of the ciliate. The sucker is in the shape of an inverted U. Thurtonia nilotica n. sp. is commensal of the digestive tract of A. nilotica. The cell is pear-shaped, with the anterior part narrowed and the posterior part swollen (110–114 µm × 85–92 µm). 46 to 50 kineties are unevenly distributed on both sides of the ciliate. The sucker is shaped like an inverted lunar crescent.